History of Mathematics in Basic Education: A Study of Undergraduate Students Graduating in Mathematics (Research, Society and Development, 2019)
Researchers in Mathematics Education have pointed out the importance of including History of Mathematics (HM) classes in Basic Education. However, some studies indicate that HM has not been widely implemented by teachers at this stage of education. One of the reasons for this may be a teachers' general lack of knowledge surrounding HM, of the specific material on HM, or of the ways of presenting it in mathematics classes. Given this fact, we conducted research at a federal university located in south Minas Gerais, Brazil, to analyze the concepts surrounding the use of History of Mathematics in Basic Education for Mathematics undergraduates who are studying to become licensed teachers. These students had at least one class subject that addressed HM. The study was conducted by collecting data via an online questionnaire that was answered by 26 undergraduate students from the university. We identified that all participants understand that HM should be used in math classes. Furthermore, they provided justifications as to why HM should be introduced at this level of education. The students also understood that HM can be used to introduce, contextualize, or explain content, or it can be used in conjunction with investigative activities. We identified that future teachers understand that "students who do not like history", "lack of time", and "lack of preparation or insecurity surrounding the use of History of Mathematics in their future classes" may be some of the challenges that they will have to face in order to teach math classes using HM.